Teacher competence development in Kurikulum Merdeka implementation: A literature study - Endang Purwati; Dadang Sukirman (Inovasi Kurikulum, 2024)
The Kurikulum Merdeka is an innovation in the world of education that requires teachers to play an active role in developing their competencies. This article aims to analyze the concept and model of teacher competency development, factors influencing teacher competency development, and effective strategies or methods for developing teacher competency in implementing the Kurikulum Merdeka. This article uses a qualitative descriptive research method by collecting literature from various sources that discuss teacher competence development. These factors influence teacher competence development and effective strategies or methods for developing teacher competence in implementing the Kurikulum Merdeka. Several significant findings from this literature review include that teachers have a strategic role in developing all aspects of human personality and abilities. Effective strategies and methods for developing teacher competency are also written, including training and development, collaboration and sharing, and the use of technology in learning. From these findings, it can be concluded that developing teacher competence in implementing the Kurikulum Merdeka requires understanding the concepts and types of teacher competence. These factors influence teacher competence development and effective strategies or methods for developing teacher competence. Hopefully, this article can provide insight and recommendations for educational practitioners in developing teacher competency in the Kurikulum Merdeka era.   Abstrak Kurikulum Merdeka Belajar merupakan inovasi dalam dunia pendidikan yang menuntut peran aktif guru dalam mengembangkan kompetensi mereka. Artikel ini bertujuan untuk menganalisis konsep dan model pengembangan kompetensi guru, faktor-faktor yang mempengaruhi pengembangan kompetensi guru, serta strategi atau metode yang efektif untuk mengembangkan kompetensi guru dalam implementasi Kurikulum Merdeka. Artikel ini menggunakan metode penelitian kualitatif deskriptif dengan mengumpulkan berbagai literatur dari berbagai sumber yang membahas tentang pengembangan kompetensi guru, faktor-faktor yang mempengaruhi pengembangan kompetensi guru, dan strategi atau metode yang efektif untuk mengembangkan kompetensi guru dalam implementasi Kurikulum Merdeka. Beberapa temuan penting dari kajian literatur ini antara lain guru memiliki peran strategis dalam mengembangkan seluruh aspek kepribadian dan kemampuan manusia. Selain itu dituliskan juga strategi dan metode yang efektif untuk mengembangkan kompetensi guru antara lain pelatihan dan pengembangan, kolaborasi dan sharing, serta penggunaan teknologi dalam pembelajaran. Dari temuan-temuan tersebut, dapat disimpulkan bahwa pengembangan kompetensi guru dalam implementasi Kurikulum Merdeka memerlukan pemahaman tentang konsep dan jenis-jenis kompetensi guru, faktor-faktor yang mempengaruhi pengembangan kompetensi guru, serta strategi atau metode yang efektif untuk mengembangkan kompetensi guru. Artikel ini diharapkan dapat memberikan wawasan dan rekomendasi bagi para praktisi pendidikan dalam mengembangkan kompetensi guru dalam era Kurikulum Merdeka. Kata Kunci: Implementasi kurikulum; kompetensi digital; kompetensi guru; Kurikulum Merdeka